Trends in the Use of Google Meet Apps for Arabic Language Learning during the COVID-19 Pandemic - Tomas, Million; Thomas, Villeda; Luciani, Chasson (Journal International of Lingua and Technology, 2023)
In the past few years, Asia has been shocked by a covid-19 outbreak with the existence of this outbreak hampering the existing work system in Asia. Thus the teaching and learning process at school is replaced by learning at home or other languages called distance learning, one way to keep the teaching and learning process going is to use Google Meet media, here the researcher has the aim of how the responses of the community and students with learning at home or distance learning using Google Meet media, and how influential it is to use Google Meet media during the pandemic. researchers conducted observations with the subject Junior High School to find out how activities in conducting the learning process online and student responses to the use of Google Meet in learning Arabic. this type of research is using quantitative research, as the object in students and teachers at Junior High School. This type of research is using quantitative research, as objects in students and teachers at Junior High School. The data collection techniques used are observation and interview techniques. The results of this study aim to help students and teachers to be able to apply the Google Meet application to the Arabic language learning process at school and can motivate students in using the application. Based on the results of observations made at Junior High School, researchers can find out the use of google meet applications and applications in Arabic language learning that can be used by educators and students. And it is hoped that further researchers can use this application in other lessons that can be applied by educators and students so that the teaching and learning process can be carried out effectively and efficiently